Toward a More Hospitable Church: A Dialectic of the Ecclesiology of Bernard Lonergan (1904-1984) and Peter C. Phan (1943-…) - Kristiatmo, Thomas (FOCUS, 2024)
This article explores the interconnection between the phenomenon of migration and ecclesiology by analyzing the thoughts of Bernard Lonergan (1904-1984) and Peter C. Phan (1943- …). Utilizing qualitative method and literature study, this research seeks to elucidate how Lonergan’s idea of historical consciousness and Phan’s theological-ecclesiological reflection upon the Church could bring about a fresh understanding of the Church which is more hospitable and hence more inclusive. This is certainly not an easy task as the Church has undergone a lot of dynamics. Looking back at the history of this more-than-two-thousand-year-old institution, one will find that it is indeed a history laden with accounts of migrations. Consequently, while Phan’s project of doing a theological reflection on migration can pave the way towards a more hospitable Church, Lonergan’s proposal to resort to historical consciousness may serve as the key element in ecclesiology.